Point-of-care measurements reveal release of purines into venous blood of stroke patients - Dale, Nicholas (Purinergic Signal, 2019)
Stroke is a leading cause of death and disability. Here, we examine whether point-of-care measurement of the purines, adenosine, inosine and hypoxanthine, which are downstream metabolites of ATP, has potential to assist the diagnosis of stroke. In a prospective observational study, patients who were suspected of having had a stroke, within 4.5 h of symptom onset and still displaying focal neurological symptoms at admission, were recruited. Clinical research staff in the Emergency Departments of two hospitals used a prototype biosensor array, SMARTCap, to measure the purines in the venous blood of stroke patients and healthy controls. In controls, the baseline purines were 7.1 ± (SD) 4.2 μM (n = 52), while in stroke patients, they were 11.6 ± 8.9 μM (n = 76). Using the National Institutes for Stoke Scale (NIHSS) to band the severity of stroke, we found that minor, moderate and severe strokes all gave significant elevation of blood purines above the controls. The purine levels fall over 24 h. This was most marked for patients with haemorrhagic strokes (5.1 ± 3.6 μM, n = 9 after 24 h). The purine levels measured on admission show a significant correlation with the volume of affected brain tissue determined by medical imaging in patients who had not received thrombolysis or mechanical thrombectomy. ClinicalTrials.gov Identifier: NCT02308605